'Social glands' in parasitoids? – convergent evolution of metapleural glands in Hymenoptera. Issue 2 (2nd April 2023) - Ulmer, Jonah M; Mikó, István; Richter, Adrian; Helms, Anjel; van de Kamp, Thomas; Krogmann, Lars
Abstract: For over a century, the metapleural gland, an exocrine gland above the hind coxa, has been thought to be a unique structure for ants (Hymenoptera: Formicidae), and regarded as a catalyst for the ecological and evolutionary success of the family. This gland is one of the most researched exocrine glands in arthropods and its anatomy, ultrastructure, and chemistry are well documented. Herein, we describe an exocrine gland from the proctotrupoid wasp Pelecinus polyturator (Hymenoptera: Pelecinidae) with a similar position, structure, and chemistry to the ant metapleural gland: it is located just above the hind coxa, corresponds to an externally concave and fenestrated atrium, is composed of class 3 gland cells, and its extract contains relatively strong acids. We discover that the pelecinid gland is associated with the dilator muscle of the first abdominal spiracle, a trait that is shared with ants, but remained overlooked, possibly due to its small diameter, or obfuscation by the extensive metapleural gland. We also provide a biomechanical argument for passive emptying of the gland in both taxa. Pelecinids and ants with metapleural glands share a close association with soil. The pelecinid metapleural gland might therefore also have an antiseptic function as suggested for ants. We examined 44 other Hymenoptera families and found no glands associated with the oclusor apodeme or any signs of external modification. Our results strongly indicate that this complex trait (anatomical & chemical) evolved independently in ants and pelecinid wasps providing an exceptional system to better understand exocrine gland evolution in Hymenoptera.